Efektivitas Penggunaan Game-Based Learning dalam Meningkatkan Pemahaman Materi IPA bagi Peserta Didik Sekolah Dasar - Lambahada, Naba; Setiawan, Dodi (Yayasan Pendidikan Intan Cendekia, 2023)
This study aims to measure the effectiveness of Game-Based Learning in improving elementary school students' understanding of science concepts. The research employs a quasi-experimental design, comparing two groups of fifth-grade students—an experimental group (using Game-Based Learning) and a control group (using conventional methods). The sample consists of 60 students, with 30 students in each group, selected through purposive sampling. Data were collected through pre-test and post-test assessments on science concept understanding, as well as a student learning satisfaction survey. A t-test analysis revealed a significant improvement in science concept comprehension among the experimental group compared to the control group (t = 4.21, p 0.05). The experimental group’s average post-test scores increased by 23.5% compared to their pre-test scores, while the control group showed only a 9.8% improvement. Additionally, the student satisfaction survey indicated that 87% of students in the experimental group felt more engaged in learning compared to 62% of students in the control group. The findings confirm that Game-Based Learning is more effective in enhancing students' comprehension of science concepts than conventional teaching methods. Furthermore, this approach significantly boosts students' motivation to learn. Therefore, integrating Game-Based Learning into elementary school curricula can serve as an effective strategy for improving science education.